ANALISIS TINGKAT PERTUMBUHAN PENERIMAAN PAJAK PENGAMBILAN BAHAN GALIAN GOLONGAN C DI KABUPATEN KEPULAUAN SANGIHE - Loong, Jessica Lianita Agnelleide; Runtu, Treesje; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2017)
Own-Source Revenue is a source of regional financial and funding of the government. One of the revenues comes from local tax, which is the tax on utilization of mineral group C, especially in Sangihe islands regency. This research was conducted to find out how big the growth rate and contribution of mineral group C-tax to original income in regency of Sangihe islands in 2011-2016. This research had used a qualitative approach to the type of descriptive research, namely analyzing the data target and realization of utilization of mineral group C in 2011 using the ratio of growth rate and contribution.The results showed the acceptance realization of mineral group C-tax still fluctuate or vary. The growth rate of mineral group C-tax in Sangihe islands regency with fluctuate number and tends to be negative. The average growth rate of mineral group C-tax reached 10.53%. The growth rate considered to be unsuccessful, this is due to lack of public awareness in paying local taxes, especially mineral group C-tax. Mineral group C ia also provide a very low contribution. The contribution of mineral group C-tax as the own -source revenue for the last six years is enough maximal and included in the criteria of